2012
DOI: 10.3390/metabo2010039
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Chemistry of Aspergillus oryzae (RIB40) and A. flavus (NRRL 3357)

Abstract: Aspergillus oryzae and A. flavus are important species in industrial biotechnology and food safety and have been some of the first aspergilli to be fully genome sequenced. Bioinformatic analysis has revealed 99.5% gene homology between the two species pointing towards a large coherence in the secondary metabolite production. In this study we report on the first comparison of secondary metabolite production between the full genome sequenced strains of A. oryzae (RIB40) and A. flavus (NRRL 3357). Surprisingly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
91
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 85 publications
10
91
0
Order By: Relevance
“…Databases of characterized natural products searchable by monoisotopic mass, such as Antibase, can assist in dereplication 130) . HPLC-DAD-MS dereplication of SM production produced by genome-sequenced strains of A. oryzae (RIB40) and A. flavus (NRRL 3357) revealed that, although bioinformatics analysis shows 99.5% gene homology between the strains, the overall chemical profiles differed significantly 131) . Orbitrap HRMS and multiple stage mass spectrometry (MS n ) was used in conjunction with SIEVE software to identify differentially expressed metabolites in control and mutant A. flavus strains (see section 5-1) 132) .…”
Section: -2 Methods Of Analysismentioning
confidence: 99%
“…Databases of characterized natural products searchable by monoisotopic mass, such as Antibase, can assist in dereplication 130) . HPLC-DAD-MS dereplication of SM production produced by genome-sequenced strains of A. oryzae (RIB40) and A. flavus (NRRL 3357) revealed that, although bioinformatics analysis shows 99.5% gene homology between the strains, the overall chemical profiles differed significantly 131) . Orbitrap HRMS and multiple stage mass spectrometry (MS n ) was used in conjunction with SIEVE software to identify differentially expressed metabolites in control and mutant A. flavus strains (see section 5-1) 132) .…”
Section: -2 Methods Of Analysismentioning
confidence: 99%
“…A comparative analysis of the chemical profiles of A. oryzae and A. flavus under 15 growth conditions has revealed that they produce very different secondary metabolites (Rank et al, 2012). No A. oryzae isolate has been found to produce aflatoxin although some isolates are able to produce CPA (Chang et al, 2009;Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Currently, more than 600 dimeric natural products have been reported to date, among which nearly 100 are dimeric diketopiperazines. [47][48][49][50][51][52][53][54][55][56][57][58][59][60] Dimeric natural products exhibit various biological activities, [49][50][51] and dimerization is thought to contribute toward conferring bioactivity to these products. 61) In this section, we will outline our study on the enzymes involved in the biosynthesis of 10 that is aimed at understanding the biosynthetic mechanism of the formation of dimeric natural products.…”
Section: Functional Analysis Of a Cytochrome P450 As Dimerization Catmentioning
confidence: 99%